A study on the preparation of oriented beta"-alumina ceramics using rod/flake-like boehmite as precursors and their properties. Issue 12 (September 2020) - Liang, Sen; Yang, Yang; Li, Kaiyun; Zhang, Xiao
Abstract: As a material for solid electrolytes and separators, beta"-Al2 O3 is widely used in sodium beta alumina. In this study, a high fraction of beta"-phase for beta"-Al2 O3 with preferred orientation was fabricated using the traditional solid-phase synthesis; and the effect of boehmite micro-structure, the aluminum source, on the phase, microstructure, mechanical properties, and conductivity properties of prepared ceramics was investigated. X-ray diffraction (XRD), and scanning electron microscopy (SEM) results illustrate that the C-axis of beta"-Al2 O3 grains was along the direction of uniaxial compression. Above all, samples made of rod-shaped boehmite exhibited a better degree of orientation (0.21) and a higher fraction of beta" phase (96 %) than samples made of flake-shaped boehmite. Meanwhile, for samples fabricated with rod-shaped boehmite, the conductivity at 350 ℃ of the sample surface parallel to the uniaxial pressure was nearly 1.5 times (1.634E-1 S cm −1 ) greater than that of surface perpendicular to the uniaxial pressure.